SEMI-ANALYTIC TECHNIQUE FOR SOLVING HIGH ORDER NONLINEAR ORDINARY INITIAL VALUE PROBLEM - Tawfiq, Luma; Abd-Al-Razak, Heba (Iraqi Journal of Science, 2024)
The aim of this paper is to present method for solving high order nonlinear ordinarydifferential equations with initial conditions using semi-analytic technique withconstructing polynomial solutions. The original problem is concerned using twopointosculatory interpolation with the fit equal numbers of derivatives at the endpoints of an interval [0, 1] and give example illustrate suggested method andaccuracy, easily implemented. The accuracy of the method is confirmed bycompared with conventional methods ( RK4, RK-Butcher, DTM ).The existence, uniqueness and sensitivity of the solution is discussed.